Acute myeloid leukemia with variant t(8;10;21). (2022) - Bacova, Barbora; Sobotka, Jiri; Kacirkova, Petra; Rivnacova, Veronika; Karlova/Zubata, Ivana; Novak, Jan
Abstract: The t(8;21)(q22;q22) is one of the most common chromosomal abnormalities in acute myeloid leukemia (AML). Approximately 3–4% of AML cases are associated with additional chromosomal abnormalities. Their impact on the prognosis of the disease remains to be established. Here we report a case of t(8;10;21) AML with mutated c-KIT that shared key morphological features with classical t(8;21) leukemias, including the M2 morphology pattern and CD34, HLA-DR phenotype. The 63-year-old female was treated with two inductioncontaining Daunoribicine and Cytarabine and four cycles of intermediate-dose Cytarabine (1.5 g/m 2 ) and achieved long-lasting remission.